Gap between the concerns of healthcare professionals and parents' perceptions regarding dietary habits for 18-month- and 3-year-old children in Japan - Midori Ishikawa; Yumiko Morinaga; Mayu Haraikawa; Yuka Akiyama; Kemal Sasaki; Saki Horie; Nobuo Yoshiike; Yoshihisa Yamazaki; Tetsuji Yokoyama (BMC, 2023)
Abstract Background A gap has been reported between healthcare professionals' (hereafter "professionals") recognition of preschool children's diets and parents' perception of concern. This study investigated the gap between the concerns reported by professionals and parents' perceptions regarding health and dietary habits by age (18 months and 3 years) and gender in Japan. Methods The study design consisted of a cross-sectional, multilevel survey. The request letters were sent to all households with target children with the cooperation of local governments. After obtaining written informed consent from parents, questionnaires were distributed to them. The survey included 30 items on children's concerns about health and dietary habits. At the health checkup, parents indicated whether they were concerned in response to each item, and responded child's height and weight and birth height and weight. Next, the professionals provided counseling to the parents at a health checkup. After that, the professionals noted their concerns in response to the same 30 items as those given to parents. The participation rates were 82.9% (18 months) and 82.8% (3 years). Data of 239 persons for 18 months and 223 persons for 3 years old were analyzed. In the statistical analysis, the items that were judged as concerning by professionals but not by parents were identified; likewise, the items that were of concern to parents but not to professionals were identified. Sensitivity, false negative rate, specificity, false positive rate, and Youden index were calculated to analyze the discordance rate for each item. Results Many parents in this study were concerned about the issues that professionals did not consider to be concerning. Moreover, the parents worried about more issues for 3-year-olds than for 18-month-olds. The items for which ≥ 10 professionals indicated concerns and with higher discordance between the professionals and parents for both boys and girls were "picky eating" for 18-month-olds and "inconsistent amount of food" for 3-year-olds. Conclusions The concerns that professionals have with respect to children's diets and the things that parents worry about show gaps. It might be necessary to provide professional counseling for parents to develop a correct understanding of their children's dietary habits.